COMBINED, FLUSS, Vienna, AustriaWolkersdorf Castle, Gallery 2 Schlossplatz 2, 2120 Wolkersdorf, Austria 3. 8. – 7. 9. 2025 - Pericleous, Vicky (My University, 2025)
Combined 2.8. – 7.9.2025 Blanka Amezkua, Uwe Bressnik, Collectif MASI, Tamara Erde, Efi Fouriki, Dimitris Georgakopoulos, Marco Goldenstein, Yioula Hadjigeorgiou, Maria Hanl, Claudia-Maria Luenig, Eleni Lyra, Cornelia Mittendorfer, Karen Ostrom, Elena Panayotova, Aemilia Papaphilippou, Yiannis Pappas, Vicky Perikleous, Karin Maria Pfeifer, Andreas Savva curated by Stratis Pantazis and Vassiliki Vayenou (GR) The group exhibition explores the various meanings of the word COMBINED, such as "to add," "to come together," and "to unite to achieve an effect," employing every form of combinatorial thinking, even that of a schema. The word's implications are metaphorically and literally closely linked to global political instability and current crises. Against this backdrop, the participating artists' works demonstrate how the mechanisms of financial and political crisis divert our attention from the devastating, irreversible effects of environmental destruction and the workings of capitalism. Furthermore, the exhibition examines multiculturalism, the systematic support of actions related to visible and invisible divisions, intolerance, misinformation, and human rights violations. Through their visual language, the participating artists explore these concepts, as well as the factors that provoke a reaction to an action largely beyond our choice and control. By defending their personal artistic freedom, they demonstrate that taking individual responsibility for our collective future is an effective way to achieve much-needed mass change. This change should be geared towards "healing," a state that ensures a sustainable coexistence between nature and humanity. The exhibition COMBINED aims to showcase the power of contemporary art to expose the conditions that foster a global political situation—a situation that increasingly ignores human values, obscures truth and justice, and openly marginalizes attempts to improve our world. Perhaps, in the spirit of humanism, we can take action to undermine the establishment that perpetuates and promotes the destruction of our inner and outer world. Vassiliki Vayenou and Stratis Pantazis, curators
Keywords: Arts; International Art Exhibition; Political & Social Contructs; Current Crises; Multiculturalism